Análisis Financiero en la Cooperativa de Ahorro y Crédito “Cariamanga Ltda.” de la ciudad de Cariamanga período 2020- 2021. - Masache Tinitana, Jennifer Elizabeth (2023)
The Curricular Integration Work entitled "FINANCIAL ANALYSIS IN THE COOPERATIVE OF SAVINGS AND CREDIT "CARIAMANGA LTDA. OF THE CITY OF CARIAMANGA PERIODS 2020-2021". It was carried out in compliance with the general objective which consisted of performing a Financial Analysis in the Savings and Credit Cooperative "Cariamanga Ltda." of the city of Cariamanga, periods 2020-2021, with the purpose of evaluating the economic-financial structure in the determined period. The work was developed with a qualitative-quantitative approach, the design is descriptive because it characterizes the economic-financial status of the entity through observation and analysis, several methods and techniques were used that allowed the collection of information for the interpretation of financial data. In order to comply with the first objective, it was necessary to evaluate the structure of the financial statements, which made it possible to perform the vertical analysis of each period analyzed, measuring the degree of representation of each account in relation to the group to which it belongs; in addition, the horizontal analysis was performed, establishing the increases and decreases of the figures in the financial statements. Likewise, in compliance with the second objective, the financial indicators of the Superintendence of Popular and Solidarity Economy (SEPS) were applied, which allowed measuring the economic- financial situation, through the use of the main indicators such as: Capital, Structure and Quality of Assets, Microeconomic Efficiency, Profitability, Financial Intermediation, Financial Efficiency, Liquidity and Vulnerability of the Patrimony. Finally, in order to comply with the third objective, a financial report was made to know the results of the analysis and the real situation of the cooperative, putting into consideration the conclusions and recommendations in order to help in the correct decision making. After applying the financial analysis, the most relevant conclusion is that Cooperative of Savings and Credit Cariamanga Ltda, in relation to the Equity Sufficiency indicator in the year 2020 was 67.44% and for the year 2021 it was 75.75%, evidencing that it is a low percentage in relation to the established standard, that is to say that it cannot cover possible risks, in the same way when applying the Profitability indicator it gives as a result for the year 2020 of 0.04% and in the year 2021 of 0.04% evidencing that the income is not enough to strengthen its equity, for which it is necessary to improve the strategy of the administration of the existing equity to obtain favorable surpluses. Finally, the financial report was made, helping to know in a general way the results obtained, determining the conclusions and recommendations that allowed adopting the most adequate decisions.